2012
DOI: 10.1364/josaa.29.00a366
|View full text |Cite
|
Sign up to set email alerts
|

Domain of metamers exciting intrinsically photosensitive retinal ganglion cells (ipRGCs) and rods

Abstract: Any stimulus can be described as composed of two components-a fundamental color stimulus that controls the three cone responses and a metameric black that has no effect on cones but can drive photoreceptors other than cones [e.g., rods and melanopsin expressing retinal ganglion cells (ipRGCs)]. The Cohen and Kappauf [Am. J. Psychol. 95, 537 (1982)] method is extended to calculate the black metamer basis for a limited set of band spectra. Using seven colored LEDs, the method is exploited to produce real metamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…[24][25][26] It has been confirmed that the pupil diameter increases when ipRGC and rod excitation is at a minimum. 27 Furthermore, there is strong evidence of an inhibiting influence of S-cones on ipRGCs. 22,28 We speculate that ACHM patients with absence of cone function lack this cone-related inhibition on ipRGCs.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] It has been confirmed that the pupil diameter increases when ipRGC and rod excitation is at a minimum. 27 Furthermore, there is strong evidence of an inhibiting influence of S-cones on ipRGCs. 22,28 We speculate that ACHM patients with absence of cone function lack this cone-related inhibition on ipRGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Viénot and associates (Viénot & Brettel, 2014;Viénot, Brettel, Dang, & Le Rohellec, 2012) developed a seven-primary system to study the rod and melanopsin inputs to pupil responses using a metameric black framework (Cohen & Kappauf, 1982;Wyszecki, 1958). They maintained cone excitations constant while searching for ''black metamers'' that activated both rods and melanopsin.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst these factors have been established for some time, spectral sensitivity of the pupil reflex response has increasingly become of interest (Adrian, 2003; Vienot et al, 2010), due, basically, to discovery of melanopsin-expressing intrinsically photosensitive ganglion cells (ipRGCs), which contributes significantly to light-evoked pupillary responses (Vienot et al, 2012). …”
Section: Introductionmentioning
confidence: 99%